EFFICACY OF FIRST AVAILABLE DIRECT-ACTING ANTIVIRAL AGENT IN TREATMENT OF CHRONIC HEPATITIS C; RESULTS FROM A SINGLE CENTRE IN PAKISTAN - Khan, Arif Qayyum; Mansoor, Hala; Raja, Javed Iqbal; Shahbaz, Raja Yasser; Fida, Samina; Siddique, Muhammad (Pakistan Armed Forces Medical Journal, 2020)
Objective: To determine the efficacy of dual (sofosbuvir and ribavirin) and triple therapy (sofosbuvir ribavirinpegylated interferon) for treatment of hepatitis C.Study Design: Comparative cross sectional study.Place and Duration of Study: Department of Medicine, Combined Military Hospital, Lahore, from Nov 2014 toMar 2017.Methodology: A total of 182 consecutive patients with age ≥18 years and positive HCV RNA by polymerasechain reaction were included, while patients with haemoglobin of